2009
DOI: 10.1007/s10899-009-9150-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mode of Display and Message Content of Responsible Gambling Signs for Electronic Gaming Machines on Regular Gamblers

Abstract: Harm-minimisation strategies aim to reduce gambling-related risks; however, minimal evidence supports the effectiveness of current strategies involving the placement of warning signs in gambling venues and on electronic gaming machines (EGMs). This qualitative replication study evaluated the differential effect of pop-up messages compared to static signs, and the content of messages on EGMs on recall, thoughts and behaviours assessed during the session and at two-week follow-up. In study one, 127 regular EGM g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
96
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 39 publications
4
96
0
Order By: Relevance
“…Consequently, the range of responsible gambling initiatives available has expanded considerably and now includes such diverse features as: enhanced player information and support services, selfdiagnostic tests, behavioral tracking and feedback, encouraging pre-commitment to spend and timelimits when playing, warning messages, and educational videos (e.g., Auer & Griffiths, 2013;Auer, Malischnig & Griffiths, 2013;Bernhard, Lucas, & Jang, 2006;Monaghan, 2008;2009;Wood & 5 Griffiths, 2008;Griffiths, et al 2009;Monaghan & Blaszczynski, 2007;2010a;2010b;Nisbet, 2005;Sharpe et al, 2005;Williams, West & Simpson, 2007;Wohl et al, 2010;2011;Wood & Bernhard, 2010).…”
Section: "Responsible Gambling Refers To Policies and Practices Desigmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the range of responsible gambling initiatives available has expanded considerably and now includes such diverse features as: enhanced player information and support services, selfdiagnostic tests, behavioral tracking and feedback, encouraging pre-commitment to spend and timelimits when playing, warning messages, and educational videos (e.g., Auer & Griffiths, 2013;Auer, Malischnig & Griffiths, 2013;Bernhard, Lucas, & Jang, 2006;Monaghan, 2008;2009;Wood & 5 Griffiths, 2008;Griffiths, et al 2009;Monaghan & Blaszczynski, 2007;2010a;2010b;Nisbet, 2005;Sharpe et al, 2005;Williams, West & Simpson, 2007;Wohl et al, 2010;2011;Wood & Bernhard, 2010).…”
Section: "Responsible Gambling Refers To Policies and Practices Desigmentioning
confidence: 99%
“…For example, playerdefined limits, detailed account information, behavioral feedback (alerting players to changes in their gambling behavior) and highly accessible, anonymous player support are all RG features that can be offered via online gambling sites. There are an increasing number of studies that are starting to show that such features have tangible benefits in helping players to play responsibly (e.g., Auer & Griffiths, 2013;Bernhard, Lucas, & Jang, 2006;Monaghan, 2008;2009;Monaghan & Blaszczynski, 2007;2010a;2010b;Griffiths, et al 2009;Nisbet, 2005;Sharpe et al, 2005;Williams, West & Simpson, 2007;Wohl et al 2010;2011Wood & Bernhard, 2010).…”
mentioning
confidence: 99%
“…Several studies have shown that interactive message and animated information are more efficacy in changing irrational belied patterns and behavior than static message (Auer & Griffiths, 2015;Monaghan & Blaszczynski, 2010). Social psychological models also highlight that personal attitudes and normative perceptions can be predictors of behavioral 4 intentions in disordered gambling (Larimer & Neighbors, 2003;Moore & Ohtsuka, 1999).…”
mentioning
confidence: 99%
“…In short, the following responsible gambling features were deemed relevant for consideration to online poker gambling: informed player choice (Blaszczynski et al, 2005;, voluntary self--exclusion (Griffiths et al, 2009), employee training (Giroux et al, 2009), pre--commitment (limit--setting) Blaszczynski et al, 2014), in--game feedback (messaging) , player intervention and personalised feedback Cloutier et al, 2006;Monaghan & Blaszczynski, 2010), and age restriction and verification . Blaszczynski et al (2005) argued that without informed player choice (IPC), responsible gambling is not feasible and that determining what information must be presented to individuals to make informed gambling choices must be based upon scientific research rather than common sense evaluations.…”
Section: Conceptualisation Of Responsible Gambling Strategymentioning
confidence: 99%
“…In response, there have been significant attempts to develop interruptions to dissociative states when gambling via the use of pop--up messaging (Auer & Griffiths, 2015a;Auer, Malischnig & Griffiths, 2014;Blaszczynski et al, 2014;Cloutier et al, 2006;Monaghan & Blaszczynski, 2010;Wohl et al, 2014).…”
Section: In--game Feedback ('Pop Up' Messaging)mentioning
confidence: 99%